Tribenuron methyl exposure inhibits oogenesis in zebrafish Danio rerio (Hamilton, 1822) - Akbulut, C.; Ozturk, B.; Uzun, A.; Yon, N. D. (Indian Journal of Fisheries, 2017)
Tribenuron methyl is a herbicide that is used to control annual and perennial dicots in cereals and fallow land. Pesticides can access aquatic ecosystems via groundwater and affect water quality and aquatic life. Our study evaluated histopathological effects of tribenuron methyl on ovary of the zebrafish Danio rerio (Hamilton, 1822). Ovary of the fishes in control group not exposed to the herbicide showed normal histological architecture. In the fishes exposed to tribenuron methyl, vacuolisation, edema and dysmorphism were recorded. Significant decrease in the number of primary and mature oocytes as well as dose dependent increase in the number of atretic oocytes were recorded in fishes exposed to tribenuron methyl.